Crowdfunding success: a systematic literature review 2010–2017. Issue 2 (27th April 2020) - Shneor, Rotem; Vik, Amy Ann
Abstract : Purpose: The paper takes stock of accumulated knowledge on factors impacting the success of online crowdfunding (CF) campaigns while suggesting opportunities for future research development. Design/methodology/approach: A Systematic Literature Review of 88 academic papers published between 2010 and 2017. Papers were collected from four academic databases and published in 65 different journals. The review addresses issues related to theory, methods, context, findings and gaps. Overall, the paper presents an analysis of 1, 718 associations between 111 aggregated independent variables (from 927 variables) with six main aggregated success indicators. Findings: Most research involves quantitative analyses of public data collected from reward-CF platforms. More research is required in equity, lending, donation and other CF contexts. Existing studies are mostly anchored in theories of signaling, social capital and elaboration likelihood. There is a need for wider conceptualization of success beyond financial indicators. And based on aggregated summaries of effects, the paper suggests a series of CF success models, while outlining an agenda for future research. Research limitations/implications: Studied phenomenon is in its early days of existence, and hence biased by the circumstances of a new industry. Moreover, the current review only covers published journal articles in English. Practical implications: Findings of factors impacting campaign success can inform fundraisers in building campaigns, as well as platforms in adjusting systems and services toward responsibly enhancing campaign success. Moreover, identified gaps can inform on what has not been sufficiently documented and may be a source of competitive advantage. Originality/value: A comprehensive review of research on CF success factors at factor level, a coherent agenda for future research development and a series of evidence-based models on most prevalent factors impacting CF success by CF model.